Analisa Kelaikan Fungsi Jalan Terhadap Resiko Kecelakaan Lalu Lintas Pada Simpang Utama (Studi Kasus: Jalan Bintaro Sektor 3A, Tangerang Selatan) - Wicaksono, Ario; Pratama, Romadanarto; R.M, Kenisah Firstly; Montana, Fresly Verliando; Caesar, Julio (Green Publisher Indonesia, 2025)
The main intersection of Jalan Bintaro Sector 3A is an intersection that brings business areas together with the E-commuter line transit area and the education area. The overall activity that occurs increases the value of the conflicts and can reduce the effectiveness at the intersection. In this study aims to determine the effect on the feasibility of facilities in terms of signs, road markings, and road sizes to increase the value of accident conflicts in the hope that the results of this study can be used as guidelines for improvement. This research was conducted with qualitative methods, in the form of correspondent data from road users and direct observations at intersections conducted at crucial times. Data processing is taken from some journal references and the results of the distribution of questionnaires with 50 people as correspondents with the variables studied on the user of the path. The results of the analysis with the Chi Square test (a = 5%) showed that the feasibility (p = 7.81473; RR 11.061), the variable road worthiness (p = 8.50891; RR 12.361). From the results of the analysis, as well as what has been said, it is necessary to inspect points that could potentially cause accidents after the roadworthiness standard PP. No.34 / 2006, which is carried out on a 500 meter long road at the main intersection of Jalan Bintaro Sector 3A. As well as the need for handling in the form of reaffirming road markings, granting safety mirrors, installing signs, and arranging public transport parking lanes, thus this can reduce the value of the risk of accidents on Bintaro Road Sector 3A.